If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 82 = 4x + -2(1 + -4x) 82 = 4x + (1 * -2 + -4x * -2) 82 = 4x + (-2 + 8x) Reorder the terms: 82 = -2 + 4x + 8x Combine like terms: 4x + 8x = 12x 82 = -2 + 12x Solving 82 = -2 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 82 + -12x = -2 + 12x + -12x Combine like terms: 12x + -12x = 0 82 + -12x = -2 + 0 82 + -12x = -2 Add '-82' to each side of the equation. 82 + -82 + -12x = -2 + -82 Combine like terms: 82 + -82 = 0 0 + -12x = -2 + -82 -12x = -2 + -82 Combine like terms: -2 + -82 = -84 -12x = -84 Divide each side by '-12'. x = 7 Simplifying x = 7
| -10/9*-1.1111+10 | | 4/3*6.4615-8=y | | -1/2*-5 | | -x/2+5=-1 | | x/4-2=-7 | | 4(3g-5)=52 | | 2x-1=z+2 | | (4/3x)-8=(-8/7x)+8 | | 4/3-8=-8/-7+8 | | 4/3x-8=-8/7+8 | | 0=4/3x-8 | | -4+3x+2x=36 | | 0=-8/7x+8 | | 3/4m | | 3.8x=2.6x | | 0=-8/7+8 | | m+11=5m+9 | | 1/2p-7=9(-27) | | 1/2p-7(-27) | | -34-4x=13-10x | | x^4+20x^2+64=0 | | 4/3(-8)-8 | | (4/3)(-8)-8 | | 526.25-200= | | (-8/7)*4-8 | | 8+10x=62-x | | y=(4/3)*4-8 | | b=0.06m+8.50 | | (2x^2)/(6x^2) | | 2x^2/6x^2 | | 105-3x=21x+18 | | 87-7x=20x+21 |